Early weaning stress impairs development of mucosal barrier function in the porcine intestine - Smith, Feli; Clark, Jessica E.; Overman, Beth L.; Tozel, Christena C.; Huang, Jennifer H.; Rivier, Jean E. F.; Blisklager, Anthony T.; Moeser, Adam J. (American journal of physiology: Gastrointestinal and liver physiology, 2010)
Early life stress is a predisposing factor for the development of chronic intestinal disorders in adult life. Here, we show that stress associated with early weaning in pigs leads to impaired mucosal barrier function. Early weaning (15- to 21-day weaning age) resulted in sustained impairment in intestinal barrier function, as indicated by reductions in jejunal transepithelial electrical resistance and elevations in mucosal-to-serosal flux of paracellular probes [ 3 H]mannitol and [ 14 C]inulin measured at 5 and 9 wk of age, compared with that shown in late-weaned pigs (23- to 28-day weaning age). Elevated baseline short-circuit current was observed in jejunum from early-weaned pigs and was shown to be mediated via enhanced Cl − secretion. Jejunal barrier dysfunction in early-weaned pigs coincided with increased lamina propria immune cell density particularly mucosal mast cells. The mast cell stabilizer drug sodium cromoglycolate ameliorated barrier dysfunction and hypersecretion in early-weaned pigs, demonstrating an important role of mast cells. Furthermore, activation of mast cells ex vivo with c48/80 and corticotrophin-releasing factor (CRF) in pig jejunum mounted in Ussing chambers induced barrier dysfunction and elevations in short-circuit current that were inhibited with mast cell protease inhibitors. Experiments in which selective CRF receptor antagonists were administered to early-weaned pigs revealed that CRF receptor 1 (CRFr1) activation mediates barrier dysfunction and hypersecretion, whereas CRFr2 activation may be responsible for novel protective properties in the porcine intestine in response to early life stress.